ABHAYANGA- MANEUVER FOR SUKHPRASAVA - Gupta, Arun; Dei, Laxmi Priya (International Research Journal of Ayurveda & Yoga, 2019)
Abhyang /Mardan (Massage) used to be one of the widely used labor management practice by doulas, midwives and traditional birth attendants for comforting and reassuring the patient in labor, since the time immemorial, to relieve them of pain and fatigue. In recent years, with more emphasis on hospital setting based labor& delivery and increased use of various oxytocic and analgesic drugs as gold standard practice in the labor management, this non pharmacologic treatment disappeared. Abhyanga is a time tested art and science of comforting the pain and fatigue and has been enlisted as one the labor management practice in Bṛhat-Trayī. Acharya Charak in Sharir sthana categorically mentioned its application with body sites. It is mentioned to help in the descent of the fetus and ease the parturition. Abhyanga is mentioned to make tissues pliable and soft thereby increasing the tissue compliance and helps in vayu anuloman. There is no dearth of scientific evidence which validate ayurveda’s claims of effectiveness of massage or abhyang as a non-pharmacologic measure to ease the labor and delivery. Many scientific studies vouch for analgesic, anxiolytic, stress relieving, oxytocic effects of massage / abhyanga, resulting into the easy vaginal delivery with lesser complications to both mother and child in a more natural way only aiding the physiologic process of parturition.This paper purports to review and validate the benefits of abhyanga in commencement of Sukhprasava in the light of the available scientific evidence and fill the research gap as there are very limited studies available in this niche area of ayurveda which can change the direction of Sukhprasava.